Genetic alterations in the human kidney clear cell carcinoma line Рпоч1-КК - A. A. Lushnikova; L. F. Morozova; I. S. Abramov; T. S. Dubrovina; A. V. Balbutskiy (Успехи молекулярной онкологии)
Continuous cell line Рпоч1-КК from the сollection of N. N. Blokhin Russian Cancer Research Center refers to the kidney clear cell carcinoma subtypе. It is useful for study of carcinogenesis and molecular targets for targeted therapy.Objective. Analysis of the genetic alterations in a stable cell culture Рпоч1-КК to characterize this model cell line.Results. Alterations in VHL (exons 1, 2 and 3) and TP53 genes (exons 6–10) were identified by amplification of genomic DNA followed by fragment analysis polymerase chain reaction and direct Sanger sequencing. An extended deletion in exon 1 in combination with mutation in exon 7 of VHL gene and 2 polymorphisms in exon 4 of TP53 gene were reveated. Such simultaneous alterations in 2 suppressor genes maight be one of the causes of aggressive tumor growth and its resistance to standard therapy.